2021
DOI: 10.3390/healthcare9101266
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Reserve Characteristics and Occupational Performance Implications in People with Mild Cognitive Impairment

Abstract: The Cognitive Reserve hypothesis suggests that there are individual differences in the ability to cope with the pathologic changes in Alzheimer’s Disease. The proportion of elderly individuals has increased in recent years; this increase emphasizes the importance of early detection of mild cognitive impairment and the promotion of healthy ageing. The purpose of our study is to characterize cognitive reserve and occupational performance implications in people with mild cognitive impairment. 125 patients with mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…In line with the literature, there was a positive influence of social activities on the cognitive status of the participants [12]. Women with MCI were found to invest more time in their social contacts and to be more active than men across all activities.…”
Section: Activity Levelsupporting
confidence: 86%
See 1 more Smart Citation
“…In line with the literature, there was a positive influence of social activities on the cognitive status of the participants [12]. Women with MCI were found to invest more time in their social contacts and to be more active than men across all activities.…”
Section: Activity Levelsupporting
confidence: 86%
“…Concerning social activities, maintaining social contacts seems to protect people with MCI against cognitive decline [ 10 , 11 ]. Other authors found that an increase in social engagement can reduce the risk of conversion to dementia [ 8 ] and identified a positive relationship between social activities and cognitive status [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Professional activity can also play a role in CR, as individuals chronically engaged in mentally stimulating activities, such as those in professions that require problem‐solving and decision‐making, tend to have a greater CR. 20 Leisure activities such as reading, playing musical instruments, and engaging in social activities can also contribute to CR. 21 These measures are often used in research studies as a way to infer CR, but they may not provide an accurate assessment of CR as they are not always directly related to CR.…”
Section: Brain and Cr/resiliencementioning
confidence: 99%